The effects of balanced low calorie diet on body composition and serum leptin of obese women (Faculty of Medicine Universitas Indonesia, 2005)
The effect of balanced low-calorie diet for 14 days on body weight (BW), body mass index (BMI), total skin fold thickness (SFT), fat mass (FM), fat free mass (FFM), waist to hip ratio (WHR) and serum leptin level was evaluated by using a pre and post-experimental balanced low-calorie diet 915.23 kcal/day with the composition of 55.81% carbohydrate, 19.46% protein and 24.73% fat for 14 days on 39 obesewomen subjects (19-55 years old) who have met the inclusion and exclusion criteria. The collected data include demographic characteristic, macronutrient and energy intake, as well as of anthropometry, FM, FFM, and serum leptin level. Body weight reduction occurs significantly (p<0.05) from 70.99 ± 8.62 to 68.81 ± 8.36 kg (3.07%); BMI reduction is significant (p<0.05) from 30.28 ± 3.11 kg/m2 to 29.36 ± 2.94 kg/m2 (3.04%); Significantly reduced SFT (p<0.05) from 99.36 ± 12.07 mm to 91.29 ± 10.85 mm (8.08%); Significantly reduced FM (p<0.05) from 35.41 ± 2.75 % to 33.65 ± 2.73% (1.76%); Significantly increased FFM percentage (p<0.05) from 64.59 ± 2.74 to 66.35 ± 2.73 (2.72%); Significantly reduced WC (waist circumference) (p<0.05) from 85.87 ± 7.31 to 83.35 ± 7.09 (2.93%); Significantly reduced HC (hip circumference) (p<0.05) from 107.59 ± 6.67 to 106.49 ± 6.37 (1.02%); Significantly reducedWHR (p<0.05) from 0.80 ± 0.05 to 0.78 ± 0.04 (2.24%); Significantly reduced serum leptin (p<0.05) from 23.31 (12.06-71.22) to 18.18 (7.90-65.11) (22.01%); positive correlation is observed between serum leptin level and FM significantly (p<0.05) before treatment (r=0.47 ; p=0.003) and after treatment (r=0.57 ; p=0.001). Balanced low-calorie diet may effectively reduce body weight, BMI, skin fold thickness, percentage of fat mass, to increase percentage of fat free mass, to reduce waist to hip ratio and serum leptin level. (Med J Indones 2005; 14: 220-4)